Provisional measures in international law : the International Court of Justice and the International Tribunal for the Law of the Sea - Rosenne, Shabtai (Oxford ; New York : Oxford University Press, 2005)
"This series has been developed in cooperation with the Project on International Courts and Tribunals."
Introducing the topic -- The statutes -- The rules -- Jurisdiction -- Duration of provisional measures -- Procedure -- A survey of the decisions.
"This series has been developed in cooperation with the Project on International Courts and Tribunals (PICT)."
Includes bibliographical references and index.
Keywords: International Court of Justice; International Tribunal for the Law of the Sea; International Court of Justice; International Tribunal for the Law of the Sea; International Court of Justice; International Tribunal for the Law of the Sea; Internationaler Gerichtshof; Internationaler Seegerichtshof; Provisional remedies; CIJ = Cour internationale de justice; Provisional remedies; Internationaal Gerechtshof; Tribunalen; Recht van de zee; Rechtsmacht; Voorlopige maatregelen; Einstweiliger Rechtsschutz; Einstweiliger Rechtsschutz